«Արցախ» և «Ղարաբաղ» տեղանունների ստուգաբանության հարցի շուրջ - Մարգարյան, Լուսինե (Մատենադարան)
The etymology of the toponyms Arts‘akh and Karabakh has been and remains a subject of discussion among specialists in linguistics and toponymy. There exist many hypotheses. All interpretations of the toponym Arts‘akh stress some geographical description: mountainous terrain, vineyard, forest area or fields. Today, thousands of years later, all these descriptions are characteristic of Arts‘akh. We tend to believe that viticulture was most important for Arts‘akh. Accordingly, the analysis of the components o / vo / rtsʻ and akh can be considered as a possible interpretation of the toponym. This is also confirmed by the etymology of the toponym Karabakh as the calque of the word “Arts‘akh” with the probable meaning “Large garden”. The interpretation of the toponym Karabakh as a black garden or a large garden should not be done solely based on the material meaning of these words. The study of historical and social-political realities as well as the alienation of Armenian toponyms suggest that Karabakh is a calque of Arts‘akh as a result of the identical perception of geographical realities. For the toponym in popular thinking would not have been so socialized if there hadnʼt been “real” and “close” translation of the denominations of the surrounding world. Therefore, we believe that Arts‘akh- Karabakh must be analyzed in one semantic field. Этимология названий “Арцах” и “Карабах” была и остается предметом обсуждений среди специалистов по лингвистике и топонимике. Во всех комментариях к названию “Арцах” за основу берется какое-либо географическое описание: виноградный сад, горная местность, лесная местность, поля. Сегодня, тысячи лет спустя, все эти описания характерны для Арцаха. Мы склонны считать, что главным для Арцаха было виноградарство. Соответственно, топоним “Арцах” можно интерпретировать посредством анализа компонентов о/во/ртс и ах. Этот вывод также подтверждается этимологией топонима “Карабах” как кальки слова “Арцах” в значении “Большой сад”. Название “Карабах” не следует интерпретировать как “черный сад” или “большой сад”, исключительно опираясь на материальный смысл этих слов. Изучение исторических и социально-политических реалий, а также факты отчуждения армянских топонимов позволяют предположить, что топоним “Карабах” – это калька “Арцаха”, вызванная идентичным восприятием географических реалий. В противном случае топоним в народном мышлении не был бы столь социализирован, если бы не действительный и “близкий” перевод наименований окружающего мира. Поэтому мы считаем, что “Арцах- Карабах” необходимо анализировать в одном смысловом поле.
Keywords: Պատմություն; Լեզվաբանություն